Colorimetric Study on Burnt Teeth and New Diagnostic Tool in Forensic Dental Identification: The Carbodent Scale - Emilio Nuzzolese; Matteo Aliberti; Giancarlo Di Vella (Oral)
Background: Teeth are the anatomical tissue with the highest resistance to the action of chemical and physical agents. This is one of the reasons that make teeth particularly useful in the identification process of skeletonized and carbonized human remains. The aim of this research is to analyze the colorimetric changes in the enamel of teeth subjected to high temperatures to develop a reproducible colorimetric cataloging method. Methods: Six groups of 21 human teeth extracted from private clinics and from a Dental School for therapeutic reasons were used and subjected to three temperature ranges in a laboratory furnace: 400 °C, 700 °C, and 1000 °C. For each temperature, two time periods of 20 min and 60 min were chosen. Each group of dental elements was analyzed using a dental spectrophotometer to extract the colorimetric data of the crown. The obtained color coordinates were subsequently converted into Red–Green–Blue (RGB) values. The two predominant colors were also selected to create average colorimetric values, which demonstrate the change in color hue according to temperature. The groups of teeth subjected to 20 min at 400 °C exhibited a dark gray coloration, while the teeth subjected to 20 min at 700 °C showed a general increase in color brightness with beige–blueish hues. Results: The teeth subjected to 20 min at 1000 °C displayed progressively lighter shades with pinkish reflections. The teeth subjected to 60 min at the same temperatures demonstrated a general increase in brightness, making differentiation more challenging, except for the group of teeth burned at 400 °C, which showed light gray–blueish tones. Conclusions: This study further supports the existing literature on the correlation between colorimetric shifts in carbonized teeth and the maximum temperature reached, providing valuable assistance to forensic pathology and the forensic dental identification of burnt human remains. Additionally, this research has led to the development of a standardized colorimetric patented scale for the observation and examination of burnt human teeth.